Epidemia discursivo-midiática de HIV/AID$: por trilhas do currículo e da produção do sujeito - Lima, Carlos Edimilson Avila de (2024)
This dissertation is epistemologically influenced by a post-critical perspective, with discursive practices having the potential to analyze not only what is said, but also what is invented when it is said. In addition, the aim is to understand how traces of a discursive-media epidemic of hiv/aid$ make it possible to compose cartographic trails addressed to a curricular arena and the production of subjectivities. With this in mind, the following specific objectives stand out: to discuss how contemporary digital platforms, such as Instagram, compose trails of sayings about subjects living with hiv/aid$; to problematize how media discourses position subjects living with hiv/aid$ and redirect relations of knowledge-power; and to understand the curricular arena produced on digital platforms as a territory in constant dispute, agency and processes of subjectivation. To this end, a cartographic sketch of discursive practices is drawn up without the pretension of elaborating universal or neutral discourses, but, above all, as traces and other clues, which undertaken on digital platforms/social networks such as Instagram, address the production of subjectivities of people living with HIV (pvh). Thus, in the analytical exercise, there are research findings that flirt with three (indications of) discursive operators of the norm via Instagram, which at the same time as infecting and repositioning a norm, also invent and viralize other wills of the norm: [Norm -1] Subject in debt; [Norm 0] Negotiation of Intimacy; and [Norm 1] Viral Curriculum. It should be noted that discursively operating a norm is not talking about a negative or positive pole, but about the functioning of alliances/disputes in a culture. At the same time as subjects share and collectivize their experiences as those living with hiv, making it possible, for example, to minimize prejudices/stigmas or to place agendas on political agendas, norms are also recreated and modified, re/positioning them in the contagion of a culture and the capillarity of a discursive-media hiv/aid$ epidemic. Discourses that shape the plots of a curriculum and the production of subjectivities.